AGE-RELATED AND LOCATION PECULIARITIES OF TOOTH ENAMEL RESTITUTION - А. А. Udod; А. S. Voronina (Ukrainian Medical Stomatological Academy, 2016)
Annotation. Relevance of the topic. Structural and functional acid resistance of enamel is evaluated by the test of resistance enamel, the essence of which is to assess the staining intensity of the enamel portion of the upper central incisor in equator area after pre-dosed acid exposure. Then occurs restoration (restitution) of the structure of the enamel area, which can be determined by the clinical estimation test of enamel remineralization rate. This process proceeds differently on different areas of the enamel. The aim of the study is to evaluate the rate of enamel restoration after acid-dosed action in different parts of the vestibular surface of the upper central incisors. Object and methods of research. Examination included 40 patients, distributed into two groups: the first group 20 children aged 12 years, the second group- the same quantity of examined aged 50-55 years. As- sessed the index of intensity of dental caries in terms DMFT, hygienic condition of the oral cavity under the simplified index Green-Vermillion (OHI-S) and the structural and functional acid resistance of teeth enamel as per the enamel resistance test on the vestibular surface of intact upper central incisor in equator area, the cutting edge and in the cervical area. After one day re-examination was carried out during which staining of acid-etched areas of enamel was conducted for each patient. This procedure was repeated every day till absence of enamel staining was notified. The results of the study and their discussion. Initial findings of structural and functional acid resistance of tooth enamel of all age groups of patients were fixed on the tooth cutting edge (5,10 ± 0,12 points or 3,08 ± 0,09 points, respectively). Significantly (p <0.05) the indices were lower in the equator area (5,62 ± 0,13 points or 3,34 ± 0,08 points). The lowest was acid resistance level appeared in the cervical area (6,87 ± 0,10 points or 3,66 ± 0,10 points). On the second day the results of the first group of children displayed the most significant recovery of enamel in the cervix and the equator area, and the intensity of staining on the average was 4,25 ± 0,14 points and 5,52±0,13 points, respectively; in the area of cutting edge - 4,42 ± 0,11 points. A second group of patients displayed more active recovery in the areas of equator and the cutting edge, where the intensity of staining at the average was 2,13 ± 0,10 points and 1,90 ± 0,12 points, respectively. This process was slower in the cervical area (2,95 ± 0,11 points). On average for the full restoration of the structure of the enamel surface in the equator area of the upper central incisor in the first group took 4,85 ± 0,12 days, in the cervical area - 5,73 ± 0,16 days, in the area of the cutting edge - 6,15 ± 0 17 days. Individuals of the second group showed enamel complete recovery at the equator area on average for a 3,52 ± 0,11 days, on the cutting edge - 3,34 ± 0,13 days, in the cervical area - for 4,38 ± 0,14 days. Conclusions. For children aged 12 years enamel restoration occurs more intensively in the equator and cervical areas, for individuals aged 50-55 years - in the equator and the cutting edge areas. A significant trend of the deterioration of the structural and functional acid resistance of enamel from the cutting edge to the cervical area was identified for both examined groups. Prospects for further research. It is planned to study the influence of tooth vital pulp and the oral fluid in restoration of acidic micro-defects of enamel in its different areas for people of different age.